Design and Simulation of Elastocaloric Refrigerator Based on Ni-Ti Plate - Chen Yanliang; Wang Yao; Sun Wen; Liu Jian; Qian Suxin (Zhileng xuebao)
Elastocaloric cooling is based on the phase transition of elastocaloric materials and is driven by uniaxial stress. Elastocaloric cooling technology affords high theoretical refrigeration efficiency and does not result in greenhouse effects; hence, it has been considered an alternative to conventional vapor compression cooling technology. This study focuses on improving the compactness of a prototype elastocaloric refrigerator developed by stretching Ni-Ti wires. Ni-Ti plates are used to substitute Ni-Ti wires as elastocaloric materials to further improve the cooling performance of the elastocaloric refrigerator. In this study, we fabricate a third-generation elastocaloric refrigerator and develop a system-simulation model to predict its performance. The performance of the third-generation prototype is significantly better than those of previous versions; the third-generation elastocaloric refrigerator achieved temperature spans of up to 12 °C and 11.4 °C under adiabatic and cooling conditions, respectively. The refrigerator affords a cooling power density of up to 0.59 W/g under the zero temperature span condition. By increasing the strain and motor speed and using thinner elastocaloric materials with higher latent heat, the third-generation refrigerator is expected to maintain a temperature of 10.7 °C in the refrigerant cabinet at an ambient temperature of 32 °C.